REGIONAL HEGEMONIC CONTENTION AND THE ASYMMETRY OF SOFT POWER: A COMPARATIVE ANALYSIS OF SOUTH AFRICA AND NIGERIA (The Strategic Review for Southern Africa, 2020)
Since 1994 when South Africa emerged from the doldrums of apartheid isolation, there has been much contention about the hegemonic profile of South Africa as well as its Nigerian counterpart whose continental leadership have reputedly held sway in Africa prior to this time. Clearly, both Nigeria and South Africa have been widely bandied as Africa's hegemonic leaders on the strength of their Afrocentric foreign policy aspirations and material as well as ideational capabilities. Specifically, this article focuses on examining how the soft power attributes of South Africa have helped to advance its hegemonic aspiration on the continent ahead of Nigeria. The article argues that although both Nigeria and South Africa have some degree of soft power attributes, South Africa has nevertheless been able to extract greater benefits from its soft power resources than its Nigerian counterpart. In doing so, it submits that the soft power assets of both countries appear asymmetrically skewed in favour of South Africa and demonstrates why this is responsible for the global preference and increasing regional recognition of South Africa as Africa's hegemonic power.